The State as an antitrust defendant - Juppet Ewing, María Fernanda (Derecho Público Iberoamericano, 2015)
This article seeks to determine the requirements for the state and its agencies can be sued for contravening antitrust regulation in the implementation of public policies. Also, try to determine where individuals who were induced by the State and its agencies to sign a contract in terms contrary to antitrust regulation can be sanctioned by the Court on account of these acts. Finally, we discuss the principle of legitimate expectations as a defense element of accountability for private agents induced to act contrary to antitrust rules by the State and its agencies, and replace it with the concept of lucid confidence.